2005
DOI: 10.1159/000089347
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Broad-Spectrum PCR Assay for Human Papillomaviruses in Screening Benign Lesions of the Upper Aerodigestive Tract

Abstract: Background: A variety of different human papillomavirus (HPV) types can be found in benign and malignant lesions of the upper aerodigestive tract. Therefore a broad-spectrum assay is needed for screening reasons. Methods: A PCR system with degenerate consensus primers originating from a very conserved region (e.g. L1) of the HPV genome was applied. The sensitivity level was improved by combining PCR and nested PCR. Results: A total of 27 biopsies from laryngeal papillomas (9), exophytic (3) and inverted (6) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Included are both case reports and larger series, comprising up to 101 samples analyzed by PCR16 and 67 papillomas examined by ISH110 (Table I). The methods used to evaluate the HPV involvement include the following: IHC,31 DB,51, 52 SB,41, 43, 45, 50, 55, 60, 69, 76 ISH,11, 32, 42, 44, 46, 47, 49, 56, 65, 70, 94, 103, 106, 108, 110, 114, 117, 120 and PCR 13, 15–18, 48, 53, 54, 57, 58, 59, 61–64, 66–68, 71–75, 77–93, 95–102, 104, 105, 107, 109, 111–113, 115, 116, 118, 119, 121. The studies were categorized into the following regions of origin: China and Taiwan, Other Asia, Africa/Middle East, Europe, North America, and South America.…”
Section: Resultsmentioning
confidence: 99%
“…Included are both case reports and larger series, comprising up to 101 samples analyzed by PCR16 and 67 papillomas examined by ISH110 (Table I). The methods used to evaluate the HPV involvement include the following: IHC,31 DB,51, 52 SB,41, 43, 45, 50, 55, 60, 69, 76 ISH,11, 32, 42, 44, 46, 47, 49, 56, 65, 70, 94, 103, 106, 108, 110, 114, 117, 120 and PCR 13, 15–18, 48, 53, 54, 57, 58, 59, 61–64, 66–68, 71–75, 77–93, 95–102, 104, 105, 107, 109, 111–113, 115, 116, 118, 119, 121. The studies were categorized into the following regions of origin: China and Taiwan, Other Asia, Africa/Middle East, Europe, North America, and South America.…”
Section: Resultsmentioning
confidence: 99%
“…The protein-DNA and DNA-DNA cross-links formed with formalin fixation hamper DNA extraction for the initial steps of PCR. Only two PCR based studies used prospectively collected frozen tissue samples [32,35] with differing detection rates (4/6 or 67% and 3/26 or 12% respectively).…”
Section: Methodology Does Not Impact Hpv Detection Rates For Ipmentioning
confidence: 99%
“…In oral benign lesions associated with HPV, a prevalence of HPV 6 and 11 was observed in squamous cell papilloma (SCP) and condyloma acuminatum, while HPV 2 and 57 were more prevalent in verruca vulgaris lesions [ 59 ]. Fischer et al suggested that the applied broad-spectrum PCR system is a reliable tool in the detection of HPV DNA in benign lesions of the upper aerodigestive tract [ 60 ]. Hoffmann et al suggested that HPV is correlated to a lesser extent to infectious mucosal lesions than to proliferative lesions.…”
Section: Introductionmentioning
confidence: 99%